Skąd Demodok znał historię Odysa - problematyka prawdy i fikcji w eposie oralnym. - Zieliński, Karol (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The naive question “Whence did Demodocus know Odysseus’ story”, put in the title above, is a point of departure for deliberations about the sources of the knowledge of epic singers and about the credibility of the stories in the Odyssey for the poet and for his audience. Many allusions scattered throughout the entire work suggest that the audience’s task is to confirm that everything said by a singer is the truth. From the point of view of the Odyssey’s author, if the events of the Trojan War and the Return of Odysseus are so popular in his time, they should be known to everyone immediately after they happened.The deeds of heroes were so great that they were handed over directly afterwards in the form of song, which was the most appropriate medium for the transmission of such information. By comparing Demodocus’song (VIII 73 ff.) with the scene of Beowulf (ll. 867 ff.) we can observe that it is the mechanism more often used in oral epic. This matter is connected with a relevant theoretical problem: how the truth and fiction are understood in oral epic and how tradition and innovation should be understood in multiform oral poetry.
Keywords: epos; kompozycja oralna; wielowersyjność; Odyseja; Homer